Social enterprise and sustainability: Lessons for Vietnamese social enterprises - Đinh, Ngọc Long (Tạp chí Khoa học HUFLIT, 2022)
Social enterprise is a term of a hybrid organization which aim to solve the market failure in a business mechanism. It encounters many problems however there has been limited empirical studies related to social enterprises. This paper aims to figure out factors that affect social enterprise to achieve sustainability. In this paper, author found out that resource management including human resources and financial resources influence the opportunities of achieving sustainability in term of growth. The study also suggests some solutions to help social enterprise could accomplish the sustainability in term of human resources and financial resources.